Effects of exogenous selenium application on quality characteristics, selenium speciation, and in vitro bioaccessibility of rice pancakes - Feiran An; Kun Zhuang; Lingling Shangguan; Lan Yao; Jun Dai (Food Chemistry: X)
Selenium is an essential trace element for human health. To date, a hotspot of functional foods is strengthening the content of organic Se in food using biological Se enrichment. Herein, Se-enriched rice pancakes were produced by directly adding different sodium selenite concentrations into the fermentation process. The effects of sodium selenite addition on the texture properties, structure, and Se species of rice pancakes were investigated. Meanwhile, the bioaccessibility of Se and the changes of Se species in Se-enriched rice pancakes were determined by digestion experiments in vitro. The results showed significant differences in hardness, adhesiveness, chewiness, porosity, and flavor substances of Se-enriched rice pancakes after adding sodium selenite (p < 0.05). In Se-enriched rice pancakes, selenocystine (SeCys2) and methylselenocysteine (MeSeCys) are the main Se species. When sodium selenite was added at 3.3 μg/mL, the maximum values of SeCys2 and MeSeCys were 328.35 ± 33.43 and 311.11 ± 49.48 μg/kg, respectively. Se bioaccessibility was negatively correlated with sodium selenite content. The electronic nose results of Se-enriched rice pancakes showed that the sulfur compounds, nitrogen substances, alcohol substances, alkane substances, alcohols, aldehydes, and ketones in rice pancakes significantly increased following sodium selenite addition. The results can provide a significant basis for developing high efficiency Se-enriched fermented food and the processing of Se-enriched rice pancakes.